Treatment and secondary prevention of venous thrombo -embolism in cancer patients - Ay, C.; Pabinger, I. (Hämostaseologie, 2012)
Cancer is a major and independent risk factor of venous thromboembolism (VTE). In clinical practice, a high number of VTE events occurs in patients with cancer, and treatment of cancer-associated VTE differs in several aspects from treatment of VTE in the general population. However, treatment in cancer patients remains a major challenge, as the risk of recurrence of VTE as well as the risk of major bleeding during anticoagulation is substantially higher in patients with cancer than in those without cancer. In several clinical trials, different anticoagulants and regimens have been investigated for treatment of acute VTE and secondary prophylaxis in cancer patients to prevent recurrence. Based on the results of these trials, anticoagulant therapy with low-molecular-weight heparins (LMWH) has become the treatment of choice in cancer patients with acute VTE in the initial period and for extended and long-term anticoagulation for 3–6 months. New oral anti-coagulants directly inhibiting thrombin or factor Xa, have been developed in the past decade and studied in large phase III clinical trials. Results from currently completed trials are promising and indicate their potential use for treatment of VTE also in cancer patients. However, the role of the new oral thrombin and factor Xa inhibitors for VTE treatment in cancer patients still has to be clarified in further studies specifically focusing on cancer-associated VTE. This brief review will summarize the current strategies of initial and long-term VTE treatment in patients with cancer and discuss the potential use of the new oral anticoagulants.
Keywords: Venous thromboembolism; cancer; anti -coagulation; treatment; secondary prevention; secondary prophylaxis